2023
DOI: 10.3389/fphar.2023.1154135
|View full text |Cite
|
Sign up to set email alerts
|

The application of exosomes in the early diagnosis and treatment of osteoarthritis

Abstract: With the increase in human lifespan and the aggravation of global aging, the incidence of osteoarthritis (OA) is increasing annually. To better manage and control the progression of OA, prompt diagnosis and treatment for early-stage OA are important. However, a sensitive diagnostic modality and therapy for early OA have not been well developed. The exosome is a class of extracellular vesicles containing bioactive substances, that can be delivered directly from original cells to neighboring cells to modulate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Therefore, AIS screening before the Cobb angle exceeds 40° is of significant importance for conservative treatment ( 52 , 53 ). To date, many experiments have verified the feasibility of exosome-derived miRNAs as markers for the diagnosis or treatment of diseases such as cancer ( 54 ), osteoporosis ( 55 ), osteoarthritis ( 56 ), and ankylosing spondylitis ( 57 ); however, studies on exosome-derived miRNAs in AIS patients are currently lacking. This study identified hsa-miR-27a-5p, hsa-miR-539-5p, and hsa-miR-1246 as key exosome-derived miRNAs associated with AIS, and verified that they have potential diagnostic value for AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AIS screening before the Cobb angle exceeds 40° is of significant importance for conservative treatment ( 52 , 53 ). To date, many experiments have verified the feasibility of exosome-derived miRNAs as markers for the diagnosis or treatment of diseases such as cancer ( 54 ), osteoporosis ( 55 ), osteoarthritis ( 56 ), and ankylosing spondylitis ( 57 ); however, studies on exosome-derived miRNAs in AIS patients are currently lacking. This study identified hsa-miR-27a-5p, hsa-miR-539-5p, and hsa-miR-1246 as key exosome-derived miRNAs associated with AIS, and verified that they have potential diagnostic value for AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving the bioavailability of flavonoids in Epimedium by chemical modification and other methods, and paying more attentions to other components that have the potential to treat OA, are the key to enhancing the application value of Epimedium in OA treatment. In addition, Exos have increasingly become the hot topic in the field of regenerative medicine, and play an important role in the progress and treatment of OA [ 154 , 155 ]. Whether Epimedium and its ingredients can treat OA through Exos mechanism is also one of the future research directions.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial fluid, produced by synovial membranes in joints, may contain early signs of osteoarthritis like exosomes. Studying exosomes and their contents in synovial fluid shows potential for identifying different stages of osteoarthritis ( Skriner et al, 2006 ; Chen A. et al, 2023 ).…”
Section: Exploration Of Exosomes In the Diagnosis And Treatment Of Bo...mentioning
confidence: 99%